PELATIHAN PENYELENGGARAAN JENAZAH PADA MASYARAKAT MUSLIM DI DESA PENDAWAN KECAMATAN SAMBAS - Deni Irawan; Munadi Munadi (Jurnal Pengabdian Kepada Masyarakat, 2021)
The implementation of this community service activity is designed in the form of training on funeral management which aims to provide direct knowledge about the procedures for carrying out funeral services so that it can motivate the community to continue learning and invite young people to learn it because the living must take care of the body people who have died. The targets in this training activity who can attend include the Head of Pendawan Village, Sambas District or those who represent in this case attended by the village secretary as a leader in Pendawan Village, two members of the Village Consultative Body (BPD) of Pendawan Village partners in the Village, Management The Miftahul Jannah Mosque in Pendawan Village as a partner in carrying out the training activities for the organization of bodies as many as five people, representatives of the PKK women in Pendawan Village as training participants, five members of the Miftahul Jannah Mosque Congregation, Youth of the Miftahul Jannah Mosque in Pendawan Village as training participants totaling five people, IAIS Sambas Lecturers as many as two people as a team of presenters and several other invitees. This activity can run smoothly, as evidenced by the question and answer response of the community who want to know the procedures and obstacles they face while taking care of the bodies in Pendawan Village, Sambas District. The results of this activity show a strong desire from the community to learn and find solutions to fight problems related to the management of funeral arrangements that the funeral organizers themselves cannot resolve. According to fight, the issue of whether or not is to do something that is done because of the habits of the local community or the application to the corpse due to an element of demand from the heirs to do things outside of Islamic law.